Competitiveness in the traffic sign makers sector on the example of the Czmuda Company - Majewska, Katarzyna (2014)
The main focus of this study lies on the business performance of the Czmuda company, which operates in the road traffic sign maker sector. The thesis shows its position on the market and compares it with other companies operating in the same sector. Consequently, this paper aims to assess the management approaches of the studied company, as well as to find the best business strategy, which could be implemented to maintain the company’s leadership in the market. There are numerous methods and styles that businesses may use in order to attain success. Normally, these methods and strategies were used to determine the target market, encourage the prospect clients to purchase Czmuda products in order to and generate profit. In fact, this study recognizes the importance and outcome of leadership, innovation and motivation to the progress and advancement of Czmuda company. The paper introduces definitions of competition and competitiveness as the Czmuda company operates in a very competitive but also a very promising sector, which is attractive to investors. The Czmuda company has had a very good reputation on the market and it does its best to keep the position, thus the present strategy should be changed in order to adopt to the new reality. The main issues are lack of liquidity and poor motivation of employees. If the company does not want to disappear from the market in the nearest future, it should take all this factors into consideration and should change its overall strategy.